Cryptachaea pacoti, a new species of spider from Brazil (Araneae: Theridiidae), with notes on parasitoid-host interaction under the influence of abiotic factors - Araújo, Fláildo Da Silva; Brescovit, Antonio Domingos; Pereira, Luis Campili; Villanueva-Bonilla, German Antonio; Sobczak, Jober Fernando (Zootaxa, 2025)
The spider theridiid genus Cryptachaea Archer (1946) include today 112 species distributed in tropical and temperate regions worldwide. These spiders are attacked by Ichneumonidae parasitoids of the Polysphincta group of genera. In one of the remaining Atlantic Forest areas of the state of the Ceará, Brazil, we recorded the spider Cryptachaea pacoti sp. nov. (Theridiidae) being parasitized by the wasp Zatypota riverai Gauld, 1991 (Hymenoptera: Ichneumonidae). In this study we describe the new spider species C. pacoti. sp. nov. (Theridiidae); an unknown interaction between the parasitoid wasp Z. riverai (Hymenoptera: Ichneumonidae) and the spider C. pacoti sp. nov., and the correlation of abiotic factors (temperature and precipitation) on the temporal variation of the parasitism rate and total abundance of C. pacoti spiders. Our study reveals that parasitoidism is more frequent between the months of May and April and that the parasitoidism rate correlates negatively with temperature, but positively with precipitation. Although we quantified parasitized and non-parasitized spiders, we did not systematically record the life stages of all collected individuals. However, observations during the sampling period indicated that only adult and subadult spiders were parasitized, suggesting possible wasp selectivity for more developed stages of the host spider. These patterns may reflect a synchronization between the life cycles of the host and the parasitoid, influenced by the region’s humid microclimate in contrast to the surrounding semiarid environment. Precipitation did not correlate with the total abundance of spiders, but temperature negatively correlated with both spider abundance and parasitism rate, likely due to changes in microhabitat structure and wasp reproductive dynamics. The spiders likely exhibit seasonal abundance patterns related to forest formation type. While Ceará is largely characterized by the Caatinga biome's dry and hot climate, the Brejos de Altitude function as humid refuges with milder microclimates, greater vegetation cover, and high moisture retention, promoting more stable arthropod communities throughout the year.